The Educational Variables of Watching Television among Syrian Children: A Survey on the Relationship between Children and Television in Deraa - Ali Asad Watfah (Journal of Islamic Studies, 1996)
The following survey had taken place in Deraa , southern syria, during summer 1990 on a sample of about 225 of the 5th class preparatory school whose ages were between 10 and 12 years. The percentage of females was 41.14% to 58.74 males. This survey aimed to point out the relationship between television and children. and it was centered around four main problems:1- The time of watching television. 2- Favorite programs. 3- parents understanding of educational aspect of television through pointing out children's attitudes towards both television and school. Among the important results of this survey we may mention the following: 1- The children highly evaluated the importance of school as compared to television. 2- There was a big number of families who did not care about the way their children watch television programs, especially those addressed to adults Besides. they did not direct children to watch educational or scientific programs. 3- As for the relationship between the time of watching television and school. this survey points out the importance of the time of watching. It revealed that children wasted on average 10 hours a week during school time. Moreover. the period of watching is doubled during holidays , on average 21 hours, . 4- There is no statistical difference between the time of watching television according to sex variable. 5- Imported cartoons with violent characteristics engaged the first place in children's interests. and in children's answers we noted the scarcity of educational and scientific programs. This survey ended by forming a number of important recommendation which emphasised the importance of protecting children against the influences of watching television. Programs for adults, and the long time of watching television. as weIl as The necessity of controlling television watching through raising the parents' educational level regarding negative and positive aspects of television communicative action.